1998
DOI: 10.1016/s0014-5793(98)00251-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective restoration of dystrophin‐associated proteins in vivo by adenovirus‐mediated transfer of truncated dystrophin cDNAs

Abstract: A series of truncated dystrophin cDNAs (3.1^4.2 kbp) containing only three, three, two or one rod repeats with hinge 1 and 4 (named v vDysAX2, AX11, AH3, M3, respectively) or no rod repeat retaining either hinge 1 or 4 (named v vDysH1, H4, respectively) were constructed. These cDNAs were introduced into skeletal muscle of adult mdx mice using the adenovirus vector with a strong CAG promoter. v vDysAX2, AX11, AH3 and v vDysM3 expressed themselves successfully and recovered dystrophin-associated proteins effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 33 publications
(43 reference statements)
0
47
0
Order By: Relevance
“…It evokes little immune reaction and enables long-term expression of the transferred genes, although full-length dystrophin cDNA is too large to be accommodated in an AAV vector. Several micro-dystrophins, in which the rod domain is largely deleted, introduced into mdx mice, 27 were successfully expressed at the sarcolemma together with the recovery of the dystrophin-glycoprotein complex that protects muscle fibers from degeneration. 28 In order to establish an AAV vectormediated gene therapy for DMD, we investigated the effect of AAV vector-mediated gene transfer into dystrophic skeletal muscles from mdx mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It evokes little immune reaction and enables long-term expression of the transferred genes, although full-length dystrophin cDNA is too large to be accommodated in an AAV vector. Several micro-dystrophins, in which the rod domain is largely deleted, introduced into mdx mice, 27 were successfully expressed at the sarcolemma together with the recovery of the dystrophin-glycoprotein complex that protects muscle fibers from degeneration. 28 In order to establish an AAV vectormediated gene therapy for DMD, we investigated the effect of AAV vector-mediated gene transfer into dystrophic skeletal muscles from mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 We previously reported that rod-truncated micro-dystrophin, which is encoded by 3.7 kb cDNA, could effectively accumulate at the sarcolemma and recover dystrophinassociated proteins after adenovirus-mediated gene transfer into mdx skeletal muscles. 27 Later, Wang et al 28 reported the effective transfer of two kinds of micro-dystrophin cDNAs (Ͻ4.2 kb) into mdx skeletal muscle using AAV vectors. The AAV vector treatment ameliorated dystrophic pathology in mdx muscle, demonstrating micro-dystrophin cDNA to be a good candidate for insertion into the AAV vector.…”
Section: Introductionmentioning
confidence: 99%
“…Pp6 cells from the mdx muscle were transfected with 10 g of a linear plasmid encoding for the ␤-galactosidase, minidystrophin and neomycin resistance genes using the lipofectamine reagent (GIBCO BRL) according to the manufacturer's instructions. 43 At 72 h after transfection, cells were selected with 3 mg/ml of G418 (Gibco BRL) for 10 days until colonies appeared. Colonies were tested for expression of LacZ and dystrophin genes.…”
Section: Isolation Of a Clonal Population Of Purified Musclederived Cmentioning
confidence: 99%
“…9 Therefore, microdystrophin, in which most of the rod domains of dystrophin are deleted, was developed to fit into rAAV. 10,11 We and others have reported successful improvement of the dystrophic phenotype in skeletal muscles of DMD mice models following introduction of this transgene. 12,13 To achieve transduction of an entire extremity, a limb perfusion by retrograde intravenous administration of the rAAV in larger animal models is being developed.…”
Section: Introductionmentioning
confidence: 99%